Acute Post-Streptococcal Glomerulonephritis in Children - M. Yu. Kagan (Вопросы современной педиатрии)
Acute post-streptococcal glomerulonephritis is the most common form of glomerulonephritis in children, continues to be a major concern for pediatricians and nephrologists worldwide. The disease is caused by prior streptococcal infection caused by -hemolytic streptococcus of A group. Nephritis-associated plasmin receptor and streptococcal pyrogenic exotoxin B are considered to be major renotrophic antigens. Clinical findings of the disease can vary from asymptomatic gross hematuria to the full-blown acute nephritic syndrome (edema, gross hematuria, hypertension, renal failure). The main laboratory findings of acute post-streptococcal glomerulonephritis include an abnormal common urine analysis (dysmorphic erythrocytes, varying degrees of proteinuria, red blood cell casts, and segmentonuclear neutrophils), an elevated titer of antibodies to antistreptococcic antigens, and hypocomplementemia. Treatment of patients is mainly supportive and is focused upon the elimination of hypervolemia and its complications (edema, hypertension). In this situation, the most effective agents are loop diuretics and antihypertensive agents. The prognosis in children is generally favourable. The review analyses the current understanding of the pathogenesis, clinical manifestations, diagnosis, treatment and prognosis of acute post-streptococcal glomerulonephritis.